Headache attributed to cranial venous sinus stenting: A case series and literature review. (September 2019) - Su, Hui; Li, Baomin; Wang, Jun; Tian, Chenglin; Cao, Xiangyu; Du, Zhihua; Liu, Xinfeng; Liu, Ruozhuo; Yu, Shengyuan
Background: The diagnostic criteria for headache attributable to cranial venous sinus stenting were first formalized in the recently published third edition of the International Classification of Headache Disorders (ICHD-3). However, the diagnostic criteria for headache caused by cranial venous sinus stenting are based on very few data and the condition is poorly characterized. Objectives: To validate the diagnostic criteria for cranial venous sinus stenting headache by retrospectively studying the characteristics of headache in patients with isolated pulsatile tinnitus who underwent curative cranial venous sinus stenting and who had not previously complained of headache. Patients and methods: We retrospectively studied clinical, radiological, and manometric data from patients with isolated venous pulsatile tinnitus who had not previously reported headache. All patients underwent lateral sinus stenting in our institution between October 2010 and February 2018. Results: Forty eight patients, 47 females and one male, were enrolled. The mean age at symptom onset was 36.2 ± 8.7 years and the mean body mass index was 24.0 ± 3.2 kg/m 2 . Lateral sinus stenosis was evident in 47 patients and a sigmoid diverticulum in one. Fourteen patients experienced headaches after recovering from general anesthesia. All were female, with a mean age of 35.5 ± 9.6 years. Headache persisted for less than 3 days in six patients (42.8%); for 3 days to 3 months in four (28.6%); and for longer than 3 months in four (28.6%). The headaches were located on the same sides as the cranial venous sinus stents in 13 patients (92.9%) and were principally occipital, being oppressive in nine patients (64.3%) and of moderate intensity in seven (50%). Age at onset of pulsatile tinnitus and body mass index were significantly associated with headache ( p < 0.05; t-test). Conclusion: To the best of our knowledge, this is the first study to describe cranial venous sinus stenting headache in detail. We found that de novo headache developed after cranial venous sinus stenting, and was usually mild to moderate, unilateral, but oppressive; almost one-third of such headaches persisted for more than 3 months. Researchers and clinicians must become familiar with this headache spectrum; further prospective studies are required.